Relevansi Teori Classical Conditioning Ivan Pavlov terhadap Pembiasaan Nilai-Nilai Keislaman dalam Pendidikan Agama Islam - Mubarak, M Zaki; Ishaac, Muhamad; Fikrianoor, Ardiyan; Zaidan, Ahmad Fadhil; Hidayat, Muhammad Ferdy (An-Nuha, 2025)
This study explores the relevance of Ivan Pavlov's Classical Conditioning theory in habituating Islamic values through Islamic Religious Education (PAI). It aims to analyze how stimulus-response principles from behavioral psychology can shape students' Islamic character. Employing a qualitative library research method, the study reviews core concepts such as acquisition, extinction, generalization, and discrimination, and their application in fostering habits like praying before studying and maintaining discipline in worship. The findings highlight that consistent use of these principles, combined with a supportive and enjoyable learning environment, enhances the internalization of Islamic values. Furthermore, Pavlov’s laws—respondent conditioning and extinction—offer a pedagogical foundation for forming religious habits that support the affective and psychomotor aspects of learning. The study concludes that classical conditioning provides a strategic framework for developing PAI methods that prioritize behavioral transformation over mere cognitive instruction.